Consumer Buying Behaviour of Processed Spice Products - Indumati, V. M.; Raveendran, N.; Sivakumar, S. D.; Balaji, P. (Indian Journal of Marketing, 2007)
Spices have been an integral part in every Indian food, be it prepared at home or elsewhere. In recent times, large scale production of spice powders, curry seasonings, masala powders, spice paste etc., has been taken up by many firms. Marketing of these brands has been aggressive since there are several brands firmly rooted in the market. Information on the buying behavior of consumers with regard to processed spices, factors influencing the purchase of processed spices and problems in use of processed spices would help firms to formulate their marketing strategies. Hence a study was undertaken addressing the above issues. The study was conducted in Bangalore and Chennai city since they were developed urban areas and the use of processed spics is likely to be higher than in other areas. Simple random sampling technique was used to select area, supermarkets and ultimately 200 sample respondents. The data required for the study were gathered by personal interview with the selected respondents. Majority of the consumers in Bangalore and Chennai purchased 200 gms of spice powders and masalas and 100 gms of spice paste per month. About 50 per cent of consumers purchased processed spices once in a month. In Bangalore, occupational status of the women respondents was the most influencing factor regarding purchase of processed spices, followed by income of the family, time saved while cooking, quality certification of the product and number of working persons in the family. In Chennai, time saved while cooking was the most influencing factor followed by employment of the respondents, income status and lack of knowledge on the method of preparation of garam masalas and other spice paste items were also influencing factors or the purchase. Addition of the preservatives was stated as the main problem in the use of processed spice products followed by gradual decline in flavour and aroma after the opening of the package of processed spice products.